COMPLIANCE MEDICATION OF HYPERTENSION - Amanda Amelia; Evita Muslimah Isnanda Putri (Indonesian Journal Of Empirical Nursing Sciences, 2024)
Introduction The problem of hypertension has become a hot topic of discussion and has become one of the priority health problems in Indonesia and in the world, because hypertension is the most common cause of cardiovascular events. Hypertension is also referred to as the "silent killer" because hypertension often does not show complaints and signs and symptoms so that patients do not realize that they have hypertension. The aim of this study was to determine adherence to medication in hypertensive patients at the Trio Husada Clinic, Lowokwaru, Malang. Method This research used descriptive research design. The population in this study were all 45 patients suffering from hypertension at the Trio Husada Clinic, Lowokwaru, Malang. The sampling technique used was purposive sampling, with a sample of 30 patients. Instrumen used questionnaire based on variable compliance of taking medicine hypertension. Result Data analyzed used univariant analysis.The results showed that low compliance are 73%, and high compliance 27%. Based on the results of the study, it is expected to continue to provide information and education on a regular basis so that hypertensi patients understand the importance of medication adherence to control their hypertension